Serving those who serve?: A critical assessment of the need for a veterans' court or veterans' list in Australia. Issue 2 (3rd April 2022) - Davidson, Clare; Loughnan, Arlie; Murray, Sarah
ABSTRACT: This article assesses the need for veterans' courts or lists in Australia. While evidence suggests that former and returned service personnel are over-represented in criminal justice institutions, insufficient attention has been paid to the desirability and feasibility of a veterans' court or list in Australia. In accordance with therapeutic jurisprudence principles, a specialist court such as this would divert eligible individuals from standard court processes into a track focused on treatment and rehabilitation. In this article, we assess the available data addressing veterans' interactions with the criminal justice system and analyse the relevance of the overseas experience for Australia. We identify the considerations relevant to the establishment of a veterans' court or veterans' list and argue that a bespoke veterans' justice pathway should be considered in order to enhance the responsiveness of the criminal justice system to the specific needs of returned service personnel, and to expand the scope of therapeutic approaches to crime in Australian jurisdictions.